Mobilização de igrejas e candidatos evangélicos nas eleições municipais de 2024 = Alternativtitel: Mobilization of Churches and Evangelical Candidates in the 2024 Municipal Elections - Louback, Marcelo Lemes (Plura, revista de estudos de religião, 2025)
We analyze the electoral campaign of four evangelical candidates elected to the City Council of Campo Mourão (CMCM) in 2024, who relied on the support and involvement of the ecclesiastical structure of four religious denominations. We seek to identify and categorize the performances, electoral strategies, and politico-religious representations activated by the candidates in articulation with the churches. Simultaneously, we highlight the similarities and specificities of the actions of each denomination, since they influence the practices and discourses conveyed in each candidacy. The empirical corpus is composed of 1.952 campaign materials, including flyers, videos, stories, texts, and photographs, collected from the candidates’ social media during the electoral period. The results reveal the coordinated mobilization between the candidates and evangelical institutions, which deploy their symbolic capital and membership in the election of their representatives.